2004
DOI: 10.1159/000078807
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Cyclins D1, E and Cyclin-Dependent Kinase Inhibitors p21(Waf1/Cip1) and p27(Kip1) in Urothelial Carcinoma: Correlation with Other Cell-Cycle-Related Proteins (Rb, p53, Ki-67 and PCNA) and Clinicopathological Features

Abstract: Introduction: The expression pattern of cyclins D1 and E, as well as cyclin-dependent kinase inhibitors p21(Wa1/Cip1) and p27(Kip1) and their relationship to tumour behaviour and patients’ prognosis was examined in 142 urothelial cell carcinomas. The expression of these proteins was also analyzed along with other cell-cycle-related proteins such as: p53, pRb and the proliferation-associated indices Ki-67 and proliferating cell nuclear antigen (PCNA). Patients and Methods: These molecule markers were localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
11
0
3
Order By: Relevance
“…Within patients treated with radical cystectomy, decreased expression of cyclin E1 was significantly associated with advanced pathologic stage, lymphovascular invasion, metastases to regional lymph nodes, and bladder cancer-specific mortality after controlling for the effects of standard pathologic features. Three previous studies have shown that decreased expression of cyclin E1 is associated with worse survival in patients with bladder cancer [5][6][7][8][9]. Richter et al reported that cyclin E1 expression decreased with transition of non-muscle-invasive to muscle-invasive bladder TCC and was associated with poor all-cause survival in univariate analysis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within patients treated with radical cystectomy, decreased expression of cyclin E1 was significantly associated with advanced pathologic stage, lymphovascular invasion, metastases to regional lymph nodes, and bladder cancer-specific mortality after controlling for the effects of standard pathologic features. Three previous studies have shown that decreased expression of cyclin E1 is associated with worse survival in patients with bladder cancer [5][6][7][8][9]. Richter et al reported that cyclin E1 expression decreased with transition of non-muscle-invasive to muscle-invasive bladder TCC and was associated with poor all-cause survival in univariate analysis [5].…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, however, the association between expression of cyclin D1 and E1 with bladder cancer presence and outcomes remains inconclusive. Bladder cancer studies have been limited by small sample sizes, short follow-up, and choice of end points such as all-cause survival rather than bladder cancer-specific survival [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…p21 immunoreactivity was considered altered when tumor cells showed very little or no nuclear reactivity (<5%). 23 Nuclear p27 and cyclin E immunoreactivity were considered altered when they were less than 30% based on previously published clinically relevant levels. [8][9][10] Ki-67 was considered altered when samples demonstrated a high proliferation count of more than 10%.…”
Section: Immunohistochemical Analysis and Scoringmentioning
confidence: 99%
“…50% and 1 50% for HIF-2 ␣ . VEGF, p53, and bcl-2 estimated as the percentage of positive neoplastic cells (cytoplasmic for VEGF and bcl-2, nuclear for p53) according to previous studies [20,21] .…”
Section: Immunohistochemical Assessmentmentioning
confidence: 99%